Family control, institutional environment and cash dividend policy: Evidence from China - Zhihua Wei; Shinong Wu; Changqing Li; Wei Chen (China Journal of Accounting Research, 2011)
Using a sample of 1486 Chinese A-share listed companies for the period 2004-2008, this study empirically tests the impact of family control, institutional environment and their interaction on the cash dividend policy of listed companies. Our results indicate that (1) family firms have a lower cash dividend payout ratio and propensity to pay dividends than non-family firms; (2) a favorable regional institutional environment has a significant positive impact on the cash dividend payout ratio and propensity to pay dividends of listed companies; and (3) the impact of the regional institutional environment on cash dividends is stronger in family firms than in non-family firms. Somewhat surprisingly, we find that controlling family shareholders in China may intensify Agency Problem I (the owner-manager conflict) rather than Agency Problem II (the controlling shareholder-minority shareholder conflict), and thus have a significant negative impact on cash dividend policy. In contrast, a favorable regional institutional environment plays a positive corporate governance role in mitigating Agency Problem I and encouraging family firms to pay cash dividends.
Keywords: D18; G35; K32; 650; Family control; Institutional environment; Cash dividend; Corporate governance